Child‘s Life at the Wardship Institution as a Problem of Society - Braslauskienė, Rasa (Acta Paedagogica Vilnensia, 1999)
As we get into deeper analysis of the children without families problems, we most evidently see that their fate is inseparably connected with the family. The attention should be paid not only to asocial families but to divorced families and lonely mothers too. There are different problems and reasons under which children come to the State wardship institutions: children are lost by parents, their parents are isolated in jail, their parents are deprived of their rights, or parents are very ill.
Keywords: wardship institution; children without families; social problem; education